2017
DOI: 10.1002/elsc.201700077
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of phenolic compounds production in Salvia miltiorrhiza hairy roots by six strains of rhizosphere bacteria

Abstract: Salvia miltiorrhiza Bunge is an important herb for the treatment of cerebrovascular and cardiovascular diseases with bioactive compounds (phenolic acids and tanshinones). Abundant studies showed that tanshinones could be stimulated by biotic and abiotic stresses, but limited information is available on biosynthesis of phenolic acids promoted by biotic stresses. The aim of the present work was to isolate and identify rhizosphere bacteria which stimulated phenolic compound in Salvia miltiorrhiza hairy roots and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Previous reports have shown that several elicitors influence the production of phenolic acids [ 34 ]. These elicitors can be divided into two groups (biotic and abiotic), with the former containing both pathogenic and plant cell components [ 35 , 36 ], and the latter including Ag + [ 37 ], MeJA [ 6 ], SA [ 38 ], etc. Elicitors can affect phenolic acid compounds via transcription factors, which activate or repress the expression of enzyme genes that are engaged in the phenolic acid biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that several elicitors influence the production of phenolic acids [ 34 ]. These elicitors can be divided into two groups (biotic and abiotic), with the former containing both pathogenic and plant cell components [ 35 , 36 ], and the latter including Ag + [ 37 ], MeJA [ 6 ], SA [ 38 ], etc. Elicitors can affect phenolic acid compounds via transcription factors, which activate or repress the expression of enzyme genes that are engaged in the phenolic acid biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…and Pantoea sp. in the rhizosphere could stimulate the plant growth and synthesize of major phenolic acids in Salvia miltiorrhiza through its production of the abundant types and contents of phytohormones [ 54 ]. Elsewhere, inoculation of Trichoderma asperellum significantly increased the artemisinin concentration and dry weight of Artemisia annua L. leaves through elevated expression of artemisinin biosynthesis crucial enzymatic genes, HMGR1 , FPS , ADS , CYP71AV1 , CPR , DBR , DXS1, and DXR1 [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the relative abundance of Porphyrobacter (ASV 46), Lysobacter (ASV 85), Microbacteriaceae (ASV 105), and Gemmatimonas (ASV 107) was significantly ( p < 0.05) higher in T891 + Fu13 compared to Fu13. Porphyrobacter has been reported to be a dominant group of bacteria with degrading ability ( Hiraishi et al, 2002 ), Lysobacter is a biocontrol bacterium with great potential ( Islam, 2010 ; Zhao et al, 2017 ), Microbacteriaceae have been shown to promote weight gain in Salvia miltiorrhiza hairy roots ( You et al, 2018 ), Gemmatimonas can accelerate the nitrogen cycle and aggregate phosphate, thereby promoting plant growth ( Zhang et al, 2023b ). Randomized forest results also showed that Porphyrobacter (ASV 46) and Lysobacter (ASV 85) were the primary influencing factors ( p < 0.05) on plant disease incidence and growth, respectively.…”
Section: Discussionmentioning
confidence: 99%